Inovasi Kebijakan Komunikasi Publik Pemerintah dalam Sosialisasi Program Analog Switch Off: Studi TVRI Stasiun Nusa Tenggara Timur, Kota Kupang - Alfania Yohrinli Gracenda Tefa; Umbu T.W. Pariangu; Mariayani O. Rene (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The transition from analog to digital television broadcasting through the Analog Switch Off (ASO) policy represents a strategic government initiative to improve broadcasting quality and optimize radio frequency spectrum utilization. This study aims to analyze the implementation of public communication innovation conducted by TVRI East Nusa Tenggara Station in supporting the dissemination of the ASO policy in Kupang City. A qualitative case study approach was employed through in-depth interviews, observation, documentation, and literature review. Data were analyzed using the interactive model of Miles and Huberman by applying Rogers’ Diffusion of Innovations Theory and Edward III’s Policy Implementation Model. The findings indicate that TVRI has implemented various communication strategies through television broadcasts, social media, public service announcements, and direct community outreach. The innovation demonstrates relative advantage, compatibility, trialability, and observability, although complexity remains a challenge for certain community groups due to limited digital literacy and unequal access to information. Furthermore, policy implementation has generally been supported by effective communication, institutional commitment, adequate organizational structure, and interagency coordination, despite limitations in human resources and the coverage of public outreach. Strengthening adaptive communication strategies, expanding community education, and enhancing institutional collaboration are essential to improve public acceptance and ensure the successful implementation of digital broadcasting migration.